2010
DOI: 10.1186/1471-2458-10-248
|View full text |Cite
|
Sign up to set email alerts
|

Using family history information to promote healthy lifestyles and prevent diseases; a discussion of the evidence

Abstract: BackgroundA family history, reflecting genetic susceptibility as well as shared environmental and behavioral factors, is an important risk factor for common chronic multifactorial diseases such as cardiovascular diseases, type 2 diabetes and many cancers.DiscussionThe purpose of the present paper is to discuss the evidence for the use of family history as a tool for primary prevention of common chronic diseases, in particular for tailored interventions aimed at promoting healthy lifestyles. The following quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 64 publications
3
69
0
1
Order By: Relevance
“…Primary-care clinicians are often the first health-care providers to ascertain family health histories and refer patients for cancer screening. 34 Barriers to collecting the FMH include lack of time, 18,34 limited tools for use in primary care, 34 concerns about validity of self-reported FMH, 35 and lack of clear guidelines to assist in collecting, interpreting, and using FMH for disease risk management. 36 Some investigators have indicated that the accuracy of self-reports of FMH of cancer may be improved if tools rather than interviews are used, 34 and if information is collected outside of clinical visits, where it could be checked with relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary-care clinicians are often the first health-care providers to ascertain family health histories and refer patients for cancer screening. 34 Barriers to collecting the FMH include lack of time, 18,34 limited tools for use in primary care, 34 concerns about validity of self-reported FMH, 35 and lack of clear guidelines to assist in collecting, interpreting, and using FMH for disease risk management. 36 Some investigators have indicated that the accuracy of self-reports of FMH of cancer may be improved if tools rather than interviews are used, 34 and if information is collected outside of clinical visits, where it could be checked with relatives.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, few studies have addressed how FMH can be used to motivate individuals to adopt and maintain healthy lifestyles to reduce disease risk. 18 The aim of this study was to examine health behaviors (maintenance of healthy weight, prudent alcohol use, regular physical activity, fruit and vegetable consumption, and no smoking) of Californians who report having one or more family members with a history of cancer (primarily in first-degree relatives) as compared with health behaviors of individuals who report no FMH of cancer in a first-degree relative, with emphasis on family history of breast or ovarian cancers, CRCs, and FMH of early-onset cancer in a firstdegree relative. CRC and breast cancer screening test use is also compared among these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…FHH information takes into account inherited, environmental, and behavioral factors that influence the development of common chronic diseases and can be a powerful risk assessment tool to determine preventive actions (Claassen et al 2010;Valdez et al 2011). For most common chronic conditions such as coronary artery disease and various types of cancers, even a moderate familial risk (one first-degree relative or two seconddegree relatives from the same lineage with late-onset condition) is associated with a twofold increase of individual risk compared to the general population risk (Scheuner et al 1997).…”
Section: Sharing Family Health History (Fhh) Informationmentioning
confidence: 99%
“…Lack of impact on behavior change may be attributed to several factors. Previous studies have shown that risk counseling can impact behavior change (Claassen et al 2010;Diabetes Prevention Program Research et al 2009;Edwards et al 2000;Heideman et al 2011;Knowler et al 2002;Kreuter and Strecher 1996;Tuomilehto et al 2001). But as with all behavior change, frequent and repetitive interventions are more likely to succeed (Knowler et al 2002;Soler et al 2010;Tuomilehto et al 2001).…”
Section: Discussionmentioning
confidence: 99%